KAJIAN TERHADAP PERTIMBANGAN HAKIM DALAM MENJATUHKAN PIDANA PERCOBAAN DAN PELATIHAN KERJA TERHADAP ANAK PELAKU KEKERASAN TERHADAP ANAK (Studi Kasus Putusan Nomor 2/Pid.Sus-Anak/2022/PN Pti) - Syadida, Muhammad Daffa; Kurniawan, Itok Dwi (Sebelas Maret University, 2025)
This study aims to analyze judges' considerations in imposing criminal sentences and work training for child perpetrators in cases of violence against children, with a case study of Decision Number 2/Pid.Sus-Anak/2022/PN Pti. The research method used is a normative approach by analyzing court decision documents and related laws and regulations. The results of the study show that judges consider the principle of the best interests of the child and align it with Article 183 of the Criminal Procedure Code in making decisions. The conclusion of this study is that the application of probation and work training as an alternative to imprisonment reflects a rehabilitative approach in the juvenile criminal justice system in Indonesia.